Guidance for assessing interregional ecosystem service flows. (October 2019) - Koellner, Thomas; Bonn, Aletta; Arnhold, Sebastian; Bagstad, Kenneth J.; Fridman, Dor; Guerra, Carlos A.; Kastner, Thomas; Kissinger, Meidad; Kleemann, Janina; Kuhlicke, Christian; Liu, Jianguo; López-Hoffman, Laura; et al.
Abstract: Ecosystem services (ES) assessments commonly focus on a specific biophysical region or nation and take its geographic borders as the system boundary. Most geographical regions are, however, not closed systems but are open and telecoupled with other regions, such that the use of ES in one location is dependent on ecosystem processes and ecological management in other locations. Interregional ES flows often affect national economies and may trigger issues of national security and global equity. To date, however, methodologies for assessing interregional flows of ES have been published in dispersed literature. This paper provides a three-step guidance for how to assess four different types of interregional ES flows (traded goods, passive biophysical flows, species migration and dispersal as well as information flows). This guidance is intended to complement national and regional ecosystem assessments. The three steps are to (i) define the goal and scope of interregional ES flow assessments, (ii) quantify the interregional ES flows using a tiered approach and (iii) interpret results in terms of uncertainties, consequences and governance options. We compile different indicators for assessing interregional ES flows and evaluate their suitability for national and regional ES assessments. Finally, to assess the implications of interregional ES flows for environmental sustainability and human well-being, we relate our flow indicators to the Sustainable Development Goals. This guidance towards systematic assessment of interregional ES flows provides a first step to measure and quantify externalised environmental costs and can contribute to the development of indicators to address interregional imbalances in trade, foreign policy and beyond.